2021
DOI: 10.1038/s41598-021-02393-x
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state fermented brewer's spent grain enzymatic extract increases in vitro and in vivo feed digestibility in European seabass

Abstract: Brewer’s spent grain (BSG) is the largest by-product originated from the brewery industry with a high potential for producing carbohydrases by solid-state fermentation. This work aimed to test the efficacy of a carbohydrases-rich extract produced from solid-state fermentation of BSG, to enhance the digestibility of a plant-based diet for European seabass (Dicentrarchus labrax). First, BSG was fermented with A. ibericus to obtain an aqueous lyophilized extract (SSF-BSG extract) and incorporated in a plant-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Previously, it was observed that the BSG-extract increased cellulose and hemicellulose digestibility [31], which may also have contributed to the reduction of the oxidative intestine damage of European seabass since the dietary complex carbohydrates negatively impact fish intestine oxidative status. Moreover, by disrupting cell walls through enzymes action, embedded phenolic compounds may also become available, thus enhancing their direct antioxidant action.…”
Section: Interaction Of Bsg Diets Versus Prebsg Dietsmentioning
confidence: 98%
See 2 more Smart Citations
“…Previously, it was observed that the BSG-extract increased cellulose and hemicellulose digestibility [31], which may also have contributed to the reduction of the oxidative intestine damage of European seabass since the dietary complex carbohydrates negatively impact fish intestine oxidative status. Moreover, by disrupting cell walls through enzymes action, embedded phenolic compounds may also become available, thus enhancing their direct antioxidant action.…”
Section: Interaction Of Bsg Diets Versus Prebsg Dietsmentioning
confidence: 98%
“…The observed role of BSG-extract in increasing NSP digestibility (see [31]) may also have modulated the activity of hepatic antioxidant enzymes. The effect of dietary supplementation with exogenous enzymes on liver oxidative stress has been evaluated with variable results.…”
Section: Interaction Of Bsg Diets Versus Prebsg Dietsmentioning
confidence: 98%
See 1 more Smart Citation
“…Solid-state fermentation (SSF) technology is a promising technology for the treatment of lignocellulosic materials for various applications (Tišma et al, 2021b). Xylanase pretreatment BSG for chicken feed reduced the reduced the concentration of polymeric arabinose and xylose by 15%-30% (Denstadli et al, 2010), and the inclusion of BSG treated with SSF by Aspergillus ibericus in fish diet increased dry matter digestibility and energy (Fernandes et al, 2021). SSF was used for BSG treatment for the production of food, wherein the properties of whole-wheat bread with the addition of fermented BSG by Aspergillus awamory increase the amount of ferulic acid by 198% (Dos Santos Costa et al, 2020).…”
Section: Biochemical Transformation Of Bsg For Improved Applicability...mentioning
confidence: 99%
“…The efficiency of hydrolysis produced by such enzymes is greatly conditioned by several aspects. As an example, there may be interactions between gastric and intestinal proteases produced by fish and the exogenous enzymes that can negatively affect their potential beneficial effects [14]. Furthermore, the effectiveness of the exogenous enzymes may be greatly reduced by the high temperatures reached during feed preparation or, in the case of being applied post-extrusion via oil top coating or spraying, by the time available for the enzymatic action inside the digestive system of the species, which is closely related to gut transit rates linked to water temperature.…”
Section: Introductionmentioning
confidence: 99%